2022
DOI: 10.1002/ccr3.6330
|View full text |Cite
|
Sign up to set email alerts
|

Fatal invasive gastric mucormycosis: Two case reports

Abstract: Mucormycosis is a fungal infection affecting most commonly immunocompromised patients. Hereby, we report two cases: the first one is about a 61‐year‐old female with diabetes who presented with vomiting. The upper gastrointestinal endoscopy showed a budding grayish process which corresponded to an invasive mucormycosis in histology. As laboratory tests showed renal dysfunction, conventional amphotericin B was started at low doses since liposomal form was unavailable in Tunisia. Evolution was marked by a worseni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The patient had to stop conventional amphotericin B due to a renal function impairment; she also underwent total gastrectomy 2 months after the diagnosis but died 10 days later. 7 The male patient presented with gastric pain, vomiting, worsened general state, and fever; the upper GI endoscopy showed a bleeding gastric ulcer, and the biopsy study detected typical zygomycetes hyphae. He did not undergo specific treatment for mucormycosis, and the outcome included septic shock and hemophagocytic syndrome, dying after eight days of admission.…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…The patient had to stop conventional amphotericin B due to a renal function impairment; she also underwent total gastrectomy 2 months after the diagnosis but died 10 days later. 7 The male patient presented with gastric pain, vomiting, worsened general state, and fever; the upper GI endoscopy showed a bleeding gastric ulcer, and the biopsy study detected typical zygomycetes hyphae. He did not undergo specific treatment for mucormycosis, and the outcome included septic shock and hemophagocytic syndrome, dying after eight days of admission.…”
mentioning
confidence: 97%
“…The authors emphasized the association of mucormycosis with diabetic ketoacidosis. 1 Khsiba et al 7 reported fatal invasive gastric mucormycosis in a 61‐year‐old diabetic Tunisian woman and a previously healthy 59‐year‐old foreign man living in Tunisia. The woman had a one-week history of vomiting after 4 months of inhaled corticoids for cough, and the upper GI endoscopy with biopsy revealed invasive mucormycosis by Rhisopus arrhizus .…”
mentioning
confidence: 99%
See 2 more Smart Citations